Impulsive Buying in E-Commerce Among Generation Z (Case Study of Generation Z in Banjarmasin City) - Sucidha, Irma (International Journal of Business, Law, and Education, 2026)
This study aims to examine and analyze the influence of external stimuli and social presence on online impulsive buying behavior among Generation Z in Banjarmasin City, with browsing activity as a mediating variable. The development of the digital ecosystem has shifted Generation Z’s consumption patterns, making them more reactive to visual and social stimuli, often leading to unplanned shopping decisions. This research method uses a quantitative approach. Primary data was obtained through the distribution of online questionnaires via Google Forms to 150 Generation Z respondents in Banjarmasin City aged between 16 and 29 years. The data analysis technique applied was Structural Equation Modeling – Partial Least Squares (SEM-PLS) with the help of SmartPLS or AMOS software. The analysis stages include evaluation of the measurement model ( outer model ) to test validity and reliability, as well as evaluation of the structural model ( inner model ) to test the hypothesis. The results of the study indicate that external stimuli, presented through the utilitarian and hedonic values of online reviews, have a positive and significant influence on browsing activity . Similarly, the social presence variable formed by the elements of interactivity, vividness , and media richness, is proven to significantly trigger an increase in browsing intensity on e-commerce platforms . A crucial finding in this study is that browsing activity is proven to mediate the relationship between external stimuli and social presence on online impulsive buying behavior. Theoretically, intensive browsing activity triggers self-control fatigue ( ego depletion ), which ultimately weakens consumers’ cognitive inhibitions and encourages the satisfaction of hedonic motives through impulsive buying. Practically, this research offers implications for e-commerce players to strengthen the quality of review content and deliver immersive visual experiences to increase consumer engagement. Furthermore, these findings serve as a reminder for consumers to be more conscious about regulating the duration of product exploration to avoid excessive consumer behavior.